Sincere, Deceitful, and Ironic Communicative Acts and the Role of the Theory of Mind in Childhood - Bosco, Francesca M.; Gabbatore, Ilaria (Frontiers in Psychology, 2017)
The aim of the study is to investigate the relationship among age, first- and second-order Theory of Mind and the increasing ability of children to understand and produce different kinds of communicative acts – sincere, ironic, and deceitful communicative acts - expressed through linguistic and extralinguistic expressive means. To communicate means to modify an interlocutor's mental states (Grice, 1989), and pragmatics studies the inferential processes that are necessary to fill the gap, which often exists in human communication, between the literal meaning of a speaker’s utterance and what the speaker intends to communicate to the interlocutor. We administered brief video-clip stories showing different kinds of pragmatic phenomena – sincere, ironic, and deceitful communicative acts - and first- and second-order ToM tasks, to 120 children, ranging in age from 3 to 8 years. The results showed the existence of a trend of difficulty in children’s ability to deal with both linguistic and extralinguistic pragmatic tasks, from the simplest to the most difficult: sincere, deceitful, and ironic communicative acts. A hierarchical regression analysis indicated that age plays a significant role in explaining children’s performance on each pragmatic task. Furthermore, the hierarchical regression analysis revealed that first-order ToM has a causal role in explaining children’s performance in handling sincere and deceitful speech acts, but not irony. We did not detect any specific role for second-order ToM. Finally, ToM only partially explains the observed increasing trend of difficulty in children’s pragmatic performance: the variance in pragmatic performance explained by ToM increases between sincere and deceitful communicative acts, but not between deceit and irony. The role of inferential ability in explaining the improvement in children’s performance across the pragmatic tasks investigated is discussed.